1981
DOI: 10.1007/bf02535008
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of [1‐14C] acetate into fatty acids of the crustaceansDaphnia magna andCyclops strenus in relation to temperature

Abstract: Daphnia magna andCyclops strenus were maintained in aquaria containing sodium [1‐14C] acetate and the effect of temperature on labeling of their lipids was investigated. Incorporation of radioactivity in total lipids was slowed by a factor of 4 in cold‐exposed (5C) specimens compared to those incubated at 25 C. There was no significant difference in the distribution of label in the lipid classes of animals incubated at the two extreme temperatures. Decrease of the temperature from 25 to 5 C brought about a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
33
0
1

Year Published

1983
1983
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 18 publications
9
33
0
1
Order By: Relevance
“…Short-term (48 h) exposure to cold temperatures (4-5°C) did not cause appreciable changes in HUFA levels of D. pulex (8) or D. magna (9). These observations indicate either that Daphnia exposed to cold temperatures must be highly dependent on dietary HUFA, or that enzymes involved in the HUFA synthesis need longer adaptation periods to reach full activity.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…Short-term (48 h) exposure to cold temperatures (4-5°C) did not cause appreciable changes in HUFA levels of D. pulex (8) or D. magna (9). These observations indicate either that Daphnia exposed to cold temperatures must be highly dependent on dietary HUFA, or that enzymes involved in the HUFA synthesis need longer adaptation periods to reach full activity.…”
mentioning
confidence: 64%
“…However, Daphnia appear unable to accumulate large amounts of docosahexaenoic acid (DHA; 22:6n3), which they readily convert to EPA (6,8). Daphnia can use α-linolenic acid (ALA; 18:3n3) and linoleic acid (LIN; 18:2n6) as precursors for the synthesis of EPA and ARA, respectively (6,9,10). However, de novo rates of FA synthesis in Daphnia have been shown to be less than 2% (11).…”
mentioning
confidence: 99%
“…In contrast, Farkas et al (17) showed that some copepods, namely, Cyclops strenuus and D. magna, showed substantial FA synthesis rates. Their calculations indicated that 0.9% of the total FA were renewed in 1 h in D. magna, and they suggested that the bulk of FA accumulated in both species could be synthesized by the animals.…”
mentioning
confidence: 90%
“…Their calculations indicated that 0.9% of the total FA were renewed in 1 h in D. magna, and they suggested that the bulk of FA accumulated in both species could be synthesized by the animals. They also showed that incorporation of radioactivity from labeled acetate into total lipids was greatly affected by temperature, with large changes in the pattern of FA labeled in D. magna (17). Various other external (e.g., UV light, salinity, dissolved oxygen concentration, pH, water transparency, stressors) and internal (e.g., reproductive condition) factors may also influence zooplankton lipid composition and biosynthesis (13,(18)(19)(20).…”
mentioning
confidence: 94%
See 1 more Smart Citation